Greyhound morbidity and mortality in Australia: A descriptive analysis of reported data from regulatory racing agencies - Chang, Vysie; Descovich, Kris; Henning, Joerg; Allavena, Rachel (Frontiers in Veterinary Science, 2022)
Commercial greyhound racing is legal in Australia but controversial due to concerns around animal welfare. To make evidence-based recommendations around animal welfare standards, a comprehensive analysis of available data on race events, animal health, injuries and fatalities is required. We undertook a review of publicly available data and reports published by official greyhound racing bodies for the purpose of determining how morbidity and mortality events associated with dog training and racing could be benchmarked. Six years of available data from stewards’ reports, quarterly and annual reports were analysed from New South Wales, Victoria and Queensland. Analysis demonstrated that whole-of-life tracking for individual dogs was sparse. Although stewards’ reports were published in all three states, the availability of aggregated quarterly and annual reports varied. When available these provided additional information such as injury incidents standardised per thousand starts. In Queensland, quarterly and annual reports provided an overview of greyhound mortality and morbidity rates. Contrasting with Victoria, where quarterly reports were unavailable and only annual reports were published, meaning quarterly trends in could not be determined. Injuries categorised by severity were routinely included in quarterly reports in Queensland and New South Wales but were unavailable in Victoria. Our findings demonstrate that data recording and reporting practices must be standardised to accurately evaluate whether animal welfare standards are being met in the Australian greyhound racing industry. Our recommendation is to have national standardized reporting of injuries and deaths, and a publicly available database for whole-of-life tracking for individual racing greyhounds.